Association between METTL3 gene polymorphisms and neuroblastoma susceptibility: A nine‐centre case‐control study. Issue 16 (2nd July 2020) - Bian, Jun; Zhuo, Zhenjian; Zhu, Jinhong; Yang, Zhonghua; Jiao, Zhang; Li, Yong; Cheng, Jiwen; Zhou, Haixia; Li, Suhong; Li, Li; He, Jing; Liu, Yanfei
Abstract: Neuroblastoma ranks as the most commonly seen and deadly solid tumour in infancy. The aberrant activity of m 6 A‐RNA methyltransferase METTL3 is involved in human cancers. Therefore, functional genetic variants in the METTL3 gene may contribute to neuroblastoma risk. In the current nine‐centre case‐control study, we aimed to analyse the association between the METTL3 gene single nucleotide polymorphisms (SNPs) and neuroblastoma susceptibility. We genotyped four METTL3 gene SNPs (rs1061026 T>G, rs1061027 C>A, rs1139130 A>G, and rs1263801 G>C) in 968 neuroblastoma patients and 1814 controls in China. We found significant associations between these SNPs and neuroblastoma risk in neither single‐locus nor combined analyses. Interestingly, in the stratified analysis, we observed a significant risk association with rs1061027 AA in subgroups of children ≤ 18 months of age (adjusted OR = 1.87, 95% CI = 1.03‐3.41, P  = .040) and females (adjusted OR = 1.86, 95% CI = 1.07‐3.24, P  = .028). Overall, we identified a significant association between METTL3 gene rs1061027 C>A polymorphism and neuroblastoma risk in children ≤18 months of age and females. Our findings provide novel insights into the genetic determinants of neuroblastoma.